2022
DOI: 10.1186/s12967-022-03545-x
|View full text |Cite
|
Sign up to set email alerts
|

The BRD4 inhibitor JQ1 suppresses tumor growth by reducing c-Myc expression in endometrial cancer

Abstract: Background Endometrial cancer (EC) is the most common gynecological malignancy in developed countries. Efficacy of the bromodomain 4 (BRD4) inhibitor JQ1 has been reported for the treatment of various human cancers, but its potential impact on EC remains unclear. We therefore aimed to elucidate the function of BRD4 and the effects of JQ1 in EC in vivo and in vitro. Methods The mRNA expression of BRD4 was evaluated using datasets from The Cancer Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…BRD4, a member of the bromodomain and extraterminal domain (BET) family, has been implicated in various cancers, including endometrial cancer 24 . In our study, we observed upregulated expression of BRD4 in ECSCs compared to nonstem cancer cells.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…BRD4, a member of the bromodomain and extraterminal domain (BET) family, has been implicated in various cancers, including endometrial cancer 24 . In our study, we observed upregulated expression of BRD4 in ECSCs compared to nonstem cancer cells.…”
Section: Discussionsupporting
confidence: 49%
“…BRD4, a member of the bromodomain and extraterminal domain (BET) family, has been implicated in various cancers, including endometrial cancer. 24 In our study, we observed upregulated expression of BRD4 in ECSCs compared to nonstem cancer cells. This upregulation was accompanied by enhanced sphere formation and increased expression of stem cell markers CD44 and CD133.…”
Section: Relb Binds With P65 and Relb/p65 Complex To Facilitate The S...supporting
confidence: 54%
“…Minnelide binds to the XBP subunit of the transcription factor II H (TFIIH)-BRD4 super-enhancer complex that regulates many targets, including c-Myc expression 9 . It was also reported that the anti-tumor activity of BRD4 inhibitor in TNBC was shown to be mediated by the downregulation of Myc expression 50 . Thus, the scienti c exploratory end points included the evaluation of Myc expression and accessibility of loci for the Myc gene in pre-and post-treatment tumors 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Initial small‐molecule BET inhibitors, exemplified by JQ1, were instrumental in elucidating the oncogenic role of BET proteins and the consequent effects of BET inhibition on the expression of various oncogenes. This modulation of key oncogenes is believed to underlie the antitumorigenic properties of BET inhibitors observed in preclinical models 268,269 . Nonetheless, the clinical application of these agents has been constrained by their suboptimal pharmacokinetic profiles, including a brief half‐life and limited oral bioavailability.…”
Section: Targeting Epigenetics For Cancer Therapymentioning
confidence: 99%